2020
DOI: 10.1371/journal.pone.0240614
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific interactions among functionally diverse frugivores and their outcomes for plant reproduction: A new approach based on camera-trap data and tailored null models

Abstract: The study of plant-frugivore interactions is essential to understand the ecology and evolution of many plant communities. However, very little is known about how interactions among frugivores indirectly affect plant reproductive success. In this study, we examined direct interactions among vertebrate frugivores sharing the same fruit resources. Then, we inferred how the revealed direct interspecific interactions could lead to indirect (positive or negative) effects on reproductive success of fleshy fruited pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 84 publications
3
22
0
Order By: Relevance
“…However, we found the opposite relationship when carnivores did not coexist with lynx. In this scenario, carnivores invested foraging efforts to areas where food is easier to find, in accordance with other similar studies (Garcia et al, 2011;Selwyn et al, 2020;Virgós et al, 2010). We found that while badger visits were positively related to forest cover around pear trees in both the presence and absence of lynx, foxes only demonstrated this pattern in the predation risk scenario.…”
Section: Habitat Variables Modulate the Effect Of Predation Risk On V...supporting
confidence: 91%
See 2 more Smart Citations
“…However, we found the opposite relationship when carnivores did not coexist with lynx. In this scenario, carnivores invested foraging efforts to areas where food is easier to find, in accordance with other similar studies (Garcia et al, 2011;Selwyn et al, 2020;Virgós et al, 2010). We found that while badger visits were positively related to forest cover around pear trees in both the presence and absence of lynx, foxes only demonstrated this pattern in the predation risk scenario.…”
Section: Habitat Variables Modulate the Effect Of Predation Risk On V...supporting
confidence: 91%
“…Frugivorous mesocarnivores actively search for Iberian pear fruits because these are a predictable and valuable resource in Mediterranean ecosystems (Fedriani & Delibes, 2009a). Therefore, less frequent visits to pear trees under predation risk could be due to lower population abundances, a behavioural avoidance of agonistic encounters or a combination of both (Carreira et al, 2020; Ripple & Beschta, 2004; Selwyn et al, 2020). We identified far fewer fox individuals and recorded fewer visits in a predation risk scenario, which supports previous work by Garrote et al (2018), who proposed that in the Doñana National Park, a low frequency of fox visitation to pear fruits was likely related to a high lynx density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the microhabitat properties of deposition sites may vary between birds and mammals, with potential consequences for plant populations and communities (Jordano et al 2007). Finding more mammalian species with DNA barcoding of deposited seeds compared to focal observations is not surprising, since most mammals are nocturnal (Selwyn et al 2020). However, given that mammals can be frequent dispersers and their dispersal service complements those of avian frugivores (Jordano et al 2007, Martínez et al 2008, Tsunamoto et al 2020), the inclusion of seed sampling in mammal scats is useful to assess the influence of the whole disperser community as well as the relative contribution of mammals and birds on the regeneration process of their fleshy‐fruited plant partners.…”
Section: Discussionmentioning
confidence: 99%
“…Seed dispersal networks, for instance, have traditionally been constructed by either direct observation of frugivore visits on fruiting focal plants or by the capture of frugivores in mist‐nets and subsequent analysis of seeds and pulp remains in their scats (Olesen et al 2011, Jordano 2016). In recent years also (infra‐red) camera‐ and video‐camera traps have been used to sample seed removal interactions, which help to capture interactions by nocturnal frugivores like mammals (Schipper 2007, Zakaria and Rajpar 2010, Selwyn et al 2020). Focal plant observations by direct observations or camera trapping focus on the plant perspective and yield information on the quantitative contribution each frugivore species has on the plant species.…”
Section: Introductionmentioning
confidence: 99%